O capital humano no processo de adaptação às variações climáticas no semiárido paraibano - Lima, José Ribamar de Farias (2018)
Climate variations are daily events that affect the entire planet in a way that can be more or less harmful according to the strength of each event and the way the physical environment and beings are prepared to deal with these changes. In the past 170, the planet's climatic characteristics have undergone changes being seen as a result of the increase in radioactive forcing caused by the increased concentration of greenhouse gases in the atmosphere. The change in climatic structure leads to a variation in the natural landscapes, which respond to the climate from their ecophysiological characteristics. Based on this information, the development of a species distribution model can be constructed from the relationship between the physiological characteristics of plant and animal species and the new climatic conditions expected with the increase of global average temperature. In rural communities, the construction of subsistence processes tends to consider the uses of natural resources. A likely shift in the distribution of these resources may lead to a change in the functional structure of rural communities. This work aimed to identify the sustainable subsistence structure of a rural community in the municipality of Cabaceiras, state of Paraíba, and the variations that could occur in this structure from the distribution of the main vegetal resources used in the community. The region is marked by periods of drought and drought is the main socio-climatic event affecting the site. In this context, we start from the hypothesis that human capital, which includes among other characteristics the knowledge of the populations, would be one of the forces capable of strengthening the sustainability structure of this rural community in face of the effects of the droughts. To evaluate the community response, we initially propose an index capable of indicating the pressure that the preference of use can bring to each species, and from now on we model the distribution of the most used species. We recorded an increase in the distribution of these species that may suggest, due to their characteristics of ecological succession, a probable increase of degradation zones in the Northeast region. This information is part of the data that characterize the natural capital of the region under study. The other capital endowments that characterize sustainable livelihoods have been analyzed qualitatively in order to get a description of how each capital is influencing current livelihoods and how it could influence in the coming years. We identified that the main endowment that maintains the community structure is social capital, which is related to human and financial capital, the latter quite dependent on public income distribution programs. At the same time, local culture, which is allocated to the definition of human capital, functions as a liability in the contribution of financial capital. We propose that the community make use of its social capital as a way to influence other capital endowments, starting with the construction of structures that characterize physical capital, in order to protect natural capital resources that may become scarce during periods of drought. We believe that this set of actions can strengthen local financial capital, as well as the set of capital endowments, which would characterize a process of sustainable subsistence that could maintain the structure of the rural community.